2015
DOI: 10.1017/s1751731115000415
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and fat-soluble vitamins in horse tissues: a comparison with cattle

Abstract: Carotenoids are important for human health because of their provitamin A function among other biological actions. Their implication on consumer point of view of cattle products have been widely studied, but very little information is available for horse products. The aim of this study was to study the accumulation of carotenoids, retinoids and tocopherol by HPLC and HPLC-MS analysis in different horse tissues (plasma, milk, adipose tissue and liver) and compare it with that of cattle. Fat color was also studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…Differences between breeds in fat‐soluble vitamin transfer efficiency from feedstuffs to milk were observed for ruminants; thus, a possible breed effect cannot be excluded also for donkeys. However, Álvarez et al . reported that the concentration of retinol in milk from mares grazing from a pasture was double that reported for mares fed hay .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Differences between breeds in fat‐soluble vitamin transfer efficiency from feedstuffs to milk were observed for ruminants; thus, a possible breed effect cannot be excluded also for donkeys. However, Álvarez et al . reported that the concentration of retinol in milk from mares grazing from a pasture was double that reported for mares fed hay .…”
Section: Discussionmentioning
confidence: 94%
“…Fat in donkey milk has shown a higher concentration of C18:3 n ‐3 and n ‐3 FA, and a lower saturated FA (SFA) content than cow milk, as well as a lower n ‐6 to n ‐3 FA ratio . On the other hand, equid milk appears to have a lower fat‐soluble vitamins content ( α ‐tocopherol and retinol) than ruminant milk . The variables that are significantly associated with changes in donkey milk composition are: (i) the lactation stage; (ii) daily rhythms; and (iii) the interval between mechanical milkings .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group includes animals with a white fat that absorb little or no carotenoids and the other group includes those animals with a yellow fat which can absorb carotenoids. Pig, goat, sheep and rodents belong to the first group, whereas cattle, horses and birds are included in the second group ( Alvarez et al 2015;Green and Fascetti 2016;Schweigert 1998). Thus, for example, the color of bovine fat is due to the presence of b-carotene, the main carotenoid present, and to other pigments such as lutein (Nozi ere, Graulet, et al 2006; Strachan, Yang, and Table 1.…”
Section: Livestockmentioning
confidence: 99%
“…Regarding human foods that are produced from animals, carotenoids are found in egg yolks, poultry tissues, or the milk, liver, and adipose tissues of domesticated mammals, including cattle, horses, sheep, and goats . Furthermore, they are found in the flesh of some fish such as salmon and rainbow trout, as well as in a number of other commonly consumed marine animals (e.g., oyster, clam, scallop, mussel, and sea urchin gonads) …”
Section: Importance Of Carotenoids In Agro‐food Health and Diseasementioning
confidence: 99%